Factors influencing unemployment for fresh graduates after Covid-19 in Kelantan - Muhamad Aniq Arifin Mohd Zin; Premla Palanivelu; Norazila Arbain; Nurul Nadia Syahirah Mat Nazri (2024)
This research project aims to investigate the factors influencing unemployment among fresh graduates in Kelantan following the COVID-19 pandemic. The study focuses on understanding the relationship between unrealistic salary expectations and unemployment, as well as the impact of educational levels and university prestige on employment opportunities. The research methodology includes a comprehensive literature review to establish the theoretical framework and hypothesis development. Data collection involves an online survey and pilot test analysis, with subsequent data analysis utilizing SPSS software. The study also explores the role of government financial assistance for graduates from less prestigious universities. The research findings are expected to provide valuable insights for policymakers, educational institutions and graduates in addressing the challenges of post-pandemic unemployment. This project is organized into three main chapters: Introduction, Literature Review, and Research Methodology. The successful completion of this research project is attributed to the support and guidance of the supervisor, Dr. Shah Iskandar Fahmie Bin Ramlee, and the active participation of the study's respondents.